2011
DOI: 10.6090/jarq.45.99
|View full text |Cite
|
Sign up to set email alerts
|

Mating Sequence and Evidence for the Existence of a Female Contact Sex Pheromone in Brontispa longissima (Coleoptera: Chrysomelidae)

Abstract: To clarify the presence of a pheromone in Brontispa longissima (Coleoptera: Chrysomelidae), we observed its mating behavior and conducted a series of bioassays. When male and female B. longissima came in contact, the male was observed to hold and mount the female, extend its penis toward her abdominal tip, and copulate. The male was observed to hold the female only after he had touched her with his antennae and/or forelegs. Males showed similar mating attempts toward females killed by freezing. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In alignment with other beetles, the behaviors of B. longissima are olfactory sense driven and olfaction is important for host tree selection, aggregation and colonization. Additionally, it has been reported that the ratios of key components of the coconut palm leaf volatiles elicit attraction, aggregation and oviposition by this beetle 26 , 27 . Therefore, a better understanding of the molecular components involved in olfactory perception in this pest will increase opportunities to develop highly effective surveillance and control strategies against this beetle.…”
Section: Introductionmentioning
confidence: 95%
“…In alignment with other beetles, the behaviors of B. longissima are olfactory sense driven and olfaction is important for host tree selection, aggregation and colonization. Additionally, it has been reported that the ratios of key components of the coconut palm leaf volatiles elicit attraction, aggregation and oviposition by this beetle 26 , 27 . Therefore, a better understanding of the molecular components involved in olfactory perception in this pest will increase opportunities to develop highly effective surveillance and control strategies against this beetle.…”
Section: Introductionmentioning
confidence: 95%
“…Kawazu et al (2011) reported that males did not attempt to copulate with females that had been washed with hexane solvent. When the washed females were retreated with the hexane extract from a female body or female elytra, males resumed attempts to copulate, indicating the likely role of a female contact sex pheromone ) that we suggest is present on females regardless of age.…”
Section: Discussionmentioning
confidence: 97%
“…All observations of copulation were performed as described by Kawazu et al (2011). One male and one female were placed on a Þlter paper sheet (76 by 26 mm) surrounded by 2-mmthick slide glasses.…”
Section: Methodsmentioning
confidence: 99%
“…All observations of copulations were performed as described by Kawazu et al . (2011). In all cases, one 3-week-old virgin male and one 0-week-old initially virgin female were placed on a filter paper sheet (76 × 26 mm 2 ) (width × length) surrounded by glass (2 mm thick, placed on top).…”
Section: Methodsmentioning
confidence: 99%